Stereotactic Drainage of Brainstem Abscess With the BrainLab Varioguide (TM) System and the Airo (TM) Intraoperative CT Scanner: Technical Case Report - (:unkn) unknown (OXFORD UNIV PRESS INC, 2018)
BACKGROUND AND IMPORTANCE: Stereotactic biopsies or needle aspirations of posterior fossa lesions are technically challenging. Here we report a novel technique for performing these procedures employing the Aire (TM) intraoperative computed tomographic (CT) scanner and the VarioGuide (TM) articulated arm (BrainLab, Munich, Germany). CLINICAL PRESENTATION: A 62-yr-old woman presented with an irregularly shaped, enhancing lesion of the left pons/middle cerebellar peduncle. Slowed diffusion on magnetic resonance imaging suggested an abscess, but no definitive infectious agent/source could be identified. When the patient deteriorated despite broad-spectrum antibiotic therapy, she was taken to the operating room for stereotactic drainage of the abscess employing the described technique. A specific infectious agent (Eikenella corrodens) was identified from the aspirate, allowing for tailored antibiotic therapy. The procedure was well tolerated and the patient made a full recovery with minimal neurological sequelae. CONCLUSION: The combination of the Airo (TM) intraoperative CT and the Varioguide (TM) articulated arm allows for safe, accurate, and efficient targeting of posterior fossa lesions.
Keywords: Case report; Stereotactic surgery; Brain abscess; Brainstem lesion; MICROSURGICAL DRAINAGE; BIOPSY; LESIONS; EXPERIENCE; MANAGEMENT